1.5k views
0 votes
hi if anyone is good with extraneous solutions pleaseeeeeee help meeee tessa solves the equation below by first squaring both sides of the equation√x^2-3x-6=x-1 what extraneous solution does tessa obtain x=

2 Answers

3 votes

Answer:

its -7

Explanation:

gots it right!

User Jon Gjengset
by
5.7k points
5 votes

Answer:

x = -7/5

Explanation:

If we square both sides of the equation, we get:


√(x^2-3x-6)=x-1\\ (√(x^2-3x-6))^2=(x-1)^2\\x^2-3x-6=x^2-2x+1\\

Then, solving for x, we get:


x^2-3x-6=x^2-2x+1\\-3x-6=2x+1\\-6-1=2x+3x\\-7=5x\\(-7)/(5)=x

So, x is equal to -7/5

User Ethan Harris
by
5.4k points